Intrathecal transplantation of autologous bone marrow mononuclear cells in patients with sub-acute and chronic spinal cord injury: An open label study - Sharma, Alok; Sane, Hemangi; Gokulchandran, Nandini; Kulkarni, Pooja; Jose, Alitta; Nair, Vivek; Das, Rohit; Lakhanpal, Vaibhav; Badhe, Prerna (International Journal of Health Sciences, 2020)
Objective: The objective of the study was to analyze the effect of intrathecal transplantation of autologous bone marrow-derived mononuclear cells (BMMNCs) in functional recovery of spinal cord injury (SCI) patients along with neurorehabilitation and to evaluate various factors influencing the outcome of cellular therapy. Methods: We conducted an open-label study including 180 sub-acute and chronic SCI patients. All patients received intrathecal autologous BMMNCs along with neurorehabilitation. 80–100 mL of bone marrow was aspirated and BMMNCs were obtained using density gradient separation. An average of 1.06 × 108 cells with 97% viability was administered through lumbar puncture immediately. After transplantation, all patients underwent neurorehabilitation. Patients were followed up after an average of 9 ± 7 months. They were assessed for functional symptomatic changes and the outcome measures used were functional independence measure (FIM) and walking index for SCI (WISCI). Results: Patients showed symptomatic improvement in sitting/standing balance, bed mobility, trunk stability, upper limb function, mobility, sensation, bowel/bladder functions, and activities of daily living with no serious adverse events. Scores on FIM and WISCI showed statistically significant improvement. On subgroup analysis, it was found that early intervention and more than one dose of BMMNCs demonstrate a better functional outcome. Younger patients demonstrated better improvements in functional independence. Both cervical and dorsolumbar levels of injury show significant improvements in motor and sensory deficits. Conclusions: Autologous BMMNC transplantation with neurorehabilitation is safe, effective, enhances functional recovery, and improves the quality of life of SCI patients in sub-acute and chronic stage.